Women, Culture, and Resistance: A Feminist Critique of Minang Matrilineal Norms in Cinta Tapi Beda - Sarsono, Sarsono; Abdulloh, Abdulloh; Aprilian Luthers, Fanny Sarah; Basuki, Slamet; Muslim, Ikhwan (STIBA IEC JAKARTA, 2025)
This study investigates the representation of feminist theory within the matrilineal system of Minangkabau (Minang) culture as portrayed in the Indonesian film Cinta Tapi Beda (2012), directed by Hanung Bramantyo and Hestu Saputra. The research focuses on the conflict between the protagonist, Diana, and her mother, which reflects broader tensions between tradition, gender roles, and female autonomy. A qualitative approach was employed, utilizing textual and character analysis of selected scenes. The analysis applied key frameworks of feminist theory—postmodern, liberal, and multicultural/global feminism—to identify the intersections of feminist discourse and matrilineal values. The findings indicate that while the Minangkabau matrilineal system provides women with a degree of symbolic authority, patriarchal structures continue to dominate social and cultural practices. This tension is most visible in the rejection of Diana’s romantic relationship, shaped primarily by religious and cultural restrictions rather than the matrilineal framework itself. The study demonstrates that feminist perspectives highlight contradictions within the Minang matrilineal system, revealing how female authority remains constrained by patriarchal norms. These insights contribute to a deeper understanding of the interplay between cultural identity, gender roles, and cinematic representation in Indonesia. Future research is recommended to examine how contemporary Indonesian films further negotiate tradition and gender equality.